The dltC gene contributes to polyhexamethylene biguanide resistance in Staphylococcus aureus - Guo, Chenyang; Wang, Congcong; Chen, Qihui; Zheng, Sophia Hao; Zhang, Fengji; Yan, Jiayu; Long, Haoyang Brady; Luo, Jing; Xuan, Xiaoyan; Wang, Peng; Zheng, Huaixin (Frontiers in Microbiology, 2025)
As the efficacy of conventional antibiotics continues to decline due to antibiotic resistance, there is an urgent need for alternative antimicrobial strategies. Polyhexamethylene biguanide (PHMB), a cationic polymer with broad-spectrum antimicrobial activity and low toxicity, has been extensively used in medical and personal care applications. Although no definitive cases of bacterial resistance to PHMB have been reported, resistance to other cationic agents suggests the potential resistance to PHMB. In this study, Staphylococcus aureus was cultivated in the presence of a sublethal concentration of PHMB for 30 days, during which the organism developed inheritable resistance. A quantitative proteomics study identified differential expression of the DltC protein, which is associated with cell wall biosynthesis. Our findings revealed structural and chemical alterations in the bacterial cell wall, resulting in a surface with increased hydrophobicity, which leads to PHMB resistance. Furthermore, the adaptive PHMB-resistant strains exhibited elevated sensitivity to the hydrophobic antibiotic chloramphenicol and enhanced resistance to the hydrophilic antibiotics gentamicin and kanamycin, consistent with the resistance mechanism uncovered in this study. These results provide new insights into potential resistance mechanisms against PHMB and offer a foundation for its rational use and future antimicrobial development.